Relationship between Disease Knowledge and Self-care Adherence among Heart Failure Patients at King Abdulaziz University Hospital - Salha Hamad Alrefaei; Asmaa Kalil; Ruba Matoug Alharazi (British Journal of Healthcare and Medical Research, 2023)
Backgrounds: Heart failure (HF) is a progressive syndrome characterized by complicated therapeutic regimens and repeated hospitalizations. HF has turned into a global epidemic demonstrating serious mortality and morbidity. This study aimed to assess the relationship between disease knowledge and self-care adherence among adult HF patients at King Abdulaziz University Hospital (KAUH). Methods: A cross-sectional descriptive correlational design was utilized. Patients were recruited from outpatient clinic at KAUH in Jeddah, Saudi Arabia. A convenience sample of 208 HF patients. The Dutch Heart Failure Knowledge Scale (DHFS) and the European Heart Failure Self-Care Behavior Scale (EHFSCBs) were used to measure the main study outcomes. Participants were recruited from heart failure outpatient clinics at KAUH from January 31 – May 17, 2021. Results: 63.9% of participants were male, 49% were over 61 years old, and 30.8% of the participants were not educated. 55.8% of the participants had an adequate level of knowledge about HF disease and 57.2% had a good level of self-care adherence. The mean total HF knowledge score DHFS was 8.58±3.08 out of 15 and the self-care adherence score EHFSCBs was 28.97 ±5.61out of 60. A significant positive moderate correlation existed between disease knowledge and self-care adherence. Conclusion: Disease knowledge was adequate in more than half of the participants, and self-care adherence was good. This study has shown a relationship between disease knowledge and self-care adherence, which means that a high level of HF knowledge was associated with improved self-care adherence.